2001
DOI: 10.1097/00003643-200109000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Do patient information booklets increase perioperative anxiety?

Abstract: Patient attitudes to medical information are changing. We audited patient attitudes to an information lea¯et provided at the preadmission clinic as part of standard day-case protocol. The booklet is a simpli®ed version of the booklet Anaesthesia and Anaesthetists ± Information for Patients and Relatives published in London, UK, by the Association of Anaesthetists of Great Britain & Ireland. One hundred and three patients were surveyed before surgery over a 2-month period using an anonymous questionnaire. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Since even the modest cost of 10 pence (US$0.15) per leaflet may be seen as a reason for hospitals in the UK not to use the OAA leaflet [7], it is especially important that its effectiveness and usefulness are assessed. One consequence of providing patients with written information is the possibility of increasing their anxiety about the risks of anaesthesia [8]. However, this may not always follow [9] and we have found that most women want to know more about the specific complications of regional anaesthesia than is commonly offered [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since even the modest cost of 10 pence (US$0.15) per leaflet may be seen as a reason for hospitals in the UK not to use the OAA leaflet [7], it is especially important that its effectiveness and usefulness are assessed. One consequence of providing patients with written information is the possibility of increasing their anxiety about the risks of anaesthesia [8]. However, this may not always follow [9] and we have found that most women want to know more about the specific complications of regional anaesthesia than is commonly offered [10].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the anaesthetist explaining events and being given prior notice of proceedings (sequential order of events) were reported to be beneficial in the present study in that this helped to reduce anxiety (Table 3). Other studies have likewise revealed such information and choice to be crucial in modern elective surgery (McKenna 1997, Gillies & Baldwin 2001, Ward et al 2007). However, debate frequently occurs about the ideal time for anaesthetists to visit patients to give such information.…”
Section: Intra-operative Interventionmentioning
confidence: 98%
“…Studies on informed consent forms indicate that the presentation of benefits and harms might impact patients' pre-operative anxiety and competence to correctly assess treatment risks [55,56]. These studies primarily examine personalized information options (e.g., ITbased) and supplemental information materials in the context of shared decision-making.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 99%